RESPON PERTUMBUHAN VEGETATIF TANAMAN KANGKUNG (IPOMOEA REPTANS POIR) AKIBAT PERLAKUAN MEDIA TANAM DAN METODE PEMBERIAN AIR - M IDRIS MP (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2020)
The aims of the study were: (1) knowing the vegetative growth response of water spinach (Ipomea reptans Poir) due to the treatment of planting media; (2) knowing the vegetative growth response of water spinach plants (Ipomea reptans Poir) due to the method of giving water and (3) knowing the vegetative growth response of kale (Ipomea reptans Poir) due to a combination of planting media and methods of giving water The research was conducted at Jl. Karya Kasih, Gang. Sawah No. 1. Kelurahan. Pangkalan Masyhur, Medan Johor Subdistrict, Medan. with an altitude of ± 30 m above sea level. The research was conducted from December 2020 to February 2021. The materials used in this study were water spinach seeds, compost and top soil soil, 10 kg polybag of soil and organic pesticides for pest and disease control. Tools: moisture meter, hands prayer, hoe, machete, saw, title board, plot board and treatment board. This study used a factorial randomized block design consisting of 3 replications and 2 factors, namely: Factor I. planting medium consisting of two levels, namely: (1) M0 = 100% top soil (100% soil: 0% compost): (2) ) M1 = Compost soil ratio 3: 1 (75% soil: 25% compost) and (3) M2 = Compost soil ratio 1: 1 (50% soil: 50% compost). while, Factor II. Method of Giving Water (I) which consists of three levels, namely: (1) Po = Field Capacity by giving water once a day; (2) P1 = 3/4 Field Capacity by giving water once a day and (3) P2 = ½ Field Capacity by giving water once a day. Thus there are 9 treatment combinations and 3 replications. Observed variables include: plant height (cm), number of leaves, leaf length (cm), leaf width (cm) and plant wet weight (g). If the results of the variance test show a significant difference from the treatments tried, it can be continued with the Honestly Difference Test (DMRT) method.